Geological records of tsunamis and other extreme waves - Engel, Max; Pilarczyk, Jessica; May, Simon Matthias; Brill, Dominik; Garrett, Ed (Elsevier, 2020)
1 Introduction -- Part 2 Field methods -- 7 Geophysical prospection and sedimentological characteristics of subaquatic tsunami deposits -- 8 Ground-penetrating radar (GPR) in coastal hazard studies -- 9 Mapping of subaerial coarse clasts -- 10 Post-event field surveys -- Part 3 Fine-grained deposits -- 11 The sedimentology and geometry of fine-grained tsunami deposits from onshore environments -- 12 Foraminifera in tsunami deposits -- 13 Ostracoda in extreme-wave deposits -- 14 Diatoms in tsunami deposits -- 15 The application of molluscs for investigating tsunami deposits -- 16 Magnetic susceptibility and anisotropy of magnetic susceptibility: versatile tools to decipher hydrodynamic characteristics of past tsunamis -- 17 X-ray tomography applied to tsunami deposits -- 18 Applications of geochemical proxies in paleotsunami research -- 19 Microtextures in tsunami deposits: a useful sediment fingerprinting tool -- 20 Paleogenetic approaches in tsunami deposit studies -- 21 Post-depositional changes to tsunami deposits and their preservation potential -- 22 Erosional signatures and reorganization in ridge-and-swale sequences -- 23 Experimental and numerical models of fine sediment transport by tsunamis -- Part 4 Coarse-clast deposits -- 24 Spatial patterns of subaerial coarse clasts -- 25 Mega-tsunami deposits related to ocean island flank collapses and asteroid impacts -- 26 Erosive impact of tsunami and storm waves on rocky coasts and post-depositional weathering of coarse-clast deposits -- 27 Experimental models of coarse-clast transport by tsunamis -- 28 Reconstruction of transport modes and flow parameters from coastal boulders -- 29 Perspective of incipient motion formulas: boulder transport by high-energy waves -- Part 5 Dating -- 30 Radiocarbon dating of tsunami and storm deposits -- 31 Radiocarbon and U/Th dating of tsunami- and storm-transported coarse clasts -- 32 Optically stimulated luminescence dating of tsunami and storm deposits -- 33 Archaeological dating of tsunami and storm deposits -- 34 Tephrostratigraphy and tephrochronology -- 35 Cosmogenic nuclide dating of coarse clasts -- 36 Paleomagnetic dating of wave-emplaced boulders